HIVR4P 2016, Partnering for Prevention: Conference Summary and Highlights - Shacklett, Barbara L. (AIDS Res Hum Retroviruses, 2017)
HIV Research for Prevention: AIDS Vaccine, Microbicide, and ARV-based Prevention Science (HIVR4P) was built on a growing consensus that effective HIV prevention requires a combination of approaches and that understanding, analyzing, and debating the cross-cutting issues that impact prevention research are all essential to combat the global HIV/AIDS epidemic. To that end, the biennial HIVR4P conference is dedicated to all biomedical HIV prevention research approaches, including HIV vaccines, microbicides, pre-exposure prophylaxis, and treatment as prevention. The HIVR4P 2016 conference was held in Chicago, Illinois (USA), on October 17–21, and included more than 700 scientific presentations and 21 satellite sessions covering the latest and most promising advances across the HIV prevention research field. The theme “Partnering for Prevention” represented the conference's commitment to breaking down silos between research disciplines as well as between researchers, program developers, care providers, advocates, communities, and funders. Delegates spanning 42 countries attended the conference. One-third of those in attendance were early career investigators, which reflects a firm commitment to emerging researchers and ultimately to the goal of developing a sustainable scientific enterprise well into the future. This article presents a concise summary of highlights from the conference. For a more detailed account, one may find full abstracts, daily summaries, and webcasts on the conference website at hivr4p.org.